2018
DOI: 10.1186/s12913-018-3376-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oropharyngeal dysphagia on healthcare cost and length of stay in hospital: a systematic review

Abstract: BackgroundHealthcare systems internationally are under an ever-increasing demand for services that must be delivered in an efficient, effective and affordable manner. Several patient-related and organisational factors influence health-care expenditure and utilisation, including oropharyngeal dysphagia. Here, we present a systematic review of the literature and meta-analyses investigating how oropharyngeal dysphagia influences healthcare utilisation through length of stay (LOS) and cost.MethodsUsing a standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 48 publications
1
117
0
19
Order By: Relevance
“…Patients with swallow impairment have a significant increase in pulmonary risk and mortality rates . The social, health, and economic impacts are substantial . However, the decline in swallow function may happen insidiously with the individual making compensations and adjustments to ameliorate the trouble they are experiencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with swallow impairment have a significant increase in pulmonary risk and mortality rates . The social, health, and economic impacts are substantial . However, the decline in swallow function may happen insidiously with the individual making compensations and adjustments to ameliorate the trouble they are experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…3 The social, health, and economic impacts are substantial. 6 However, the decline in swallow function may happen insidiously with the individual making compensations and adjustments to ameliorate the trouble they are experiencing. Only a small proportion of those with swallow deficits seek and receive specific treatment for their symptoms, which often coexist with other disorders and can be affected by medications, general health, and diet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to morbidity and mortality, there is monetary cost to dysphagia that affects healthcare systems and individuals worldwide. A systemic review of OD on healthcare costs and length of stay by Attrill et al found “the presence of dysphagia added 40.36% to healthcare costs across studies.” A study by Westmark, Melgaard, Rethmeier, and Ehlers looked at costs in and out of the hospital setting and found that in the geriatric dysphagia population, costs were significantly higher for those with a dysphagia diagnosis. As per Bhattacharyya's analysis of the National Health Interview Survey, it was noted that a minority of the number of persons with self‐reported dysphagia sought healthcare, and adults with reported swallowing difficulties indicated 11.6 ± 2.0 missed workdays compared with 3.4 ± 0.1 missed days per year for individuals without reported swallowing difficulty …”
Section: Statisticsmentioning
confidence: 99%
“…In addition to morbidity and mortality, there is monetary cost to dysphagia that affects healthcare systems and individuals worldwide. A systemic review of OD on healthcare costs and length of stay by Attrill et al 43 found "the presence of dysphagia added 40.36% to healthcare costs across studies." A study by Westmark, Melgaard, Rethmeier, and Ehlers 44 looked at costs in and out of the hospital setting and found that in the geriatric dysphagia population, costs were significantly higher for those with a dysphagia diagnosis.…”
Section: Economic Impactmentioning
confidence: 99%
“…Until recently there had been no systematic investigation of the impact of oropharyngeal dysphagia on healthcare utilisation and its influence on cost. However, a recent systematic review has highlighted the need to recognise oropharyngeal dysphagia as an important contributor to pressure on healthcare systems and for economic analysis to be included in research evaluating dysphagia (Attrill, White, Murray, Hammond, & Doeltgen, 2018). An increase of 40.36% was found in dysphagia related expenditure compared with non-dysphagic groups, and dysphagia related length of stay was significantly longer with a mean addition of four extra days.…”
Section: Dysphagia and Related Toxicitiesmentioning
confidence: 99%